Occupational Well-Being of School Staff in Full Day and Half Day School Teachers - Ulifa Rahma; Yulia Dwi Anggreni; Faizah Faizah; Yuliezar Perwira Dara (Guidena)
This research is a phenomenology study in qualitative about the portrayal of occupational well-being of school staff at Full Day School and Half Day School in Senior High School teachers, which is based on Saaranen's theory (2012). The interviews were used as data. Purposive sampling, eight primary teachers were selected, including four teachers from Universitas Negeri Malang Laboratory Senior High School as the full-day school and four teachers from Panjura Senior High School as a half-day school. Milles and Huberman were used as the data analysis following by triangulation techniques. The results showed that full-day and half-day schools needed to maintain the positive aspects that were fulfilled and improve improvement. A full-day school, the elements that have fulfilled are the workers' health and resources, professional competence, working conditions, and working communities. Meanwhile, the factors that have fulfilled are the aspects of the working community, the workers’ health and resources, and professional competence at half day school. In contrast, the element that needs to improve in this school is working conditions.